Across the bay - Aponte, Carlos (Graphic artist) (Penguin Workshop, 2019)
Carlitos lives in a happy home with his mother, his abuela, and Coco the cat. Life in his hometown is cozy as can be, but the call of the capital city pulls Carlitos across the bay in search of his father.